Manajemen Komunikasi pada Petugas Kebersihan Kota Palembang - Dwi Maharani (MediaTor (Jurnal Komunikasi), 2018)
Public cleaning service or commonly referred to as “yellow troops” is the name for a group of professions working to clean up urban trash in the city of Palembang. Various kinds of stereotypes and prejudices arise in the community aimed at public cleaning service. Public cleaning service come from underprivileged people who have not been able to get out of the poverty line, have low educational background and never even received any education, because of low education and poverty factor, they also live in less clean settlements. As a socially meaningful reality, work as a public cleaning service is a profession. In general, the purpose of this study: is to find out how the management of communication that occurred on public cleaning service of Palembang city. The theory used is communication management theory and used qualitative research methods. Data collection techniques used was in-depth interviews, direct observation and documentation study. The result of the research is: communication management on the public cleaning service of Palembang city quite diverse as seen from interpersonal communication.